THE IMPACTS OF SUPERHERO LOCALIZATION ON CHARACTER EQUIVALENCE AND NARRATIVE IDENTITY - Nurul Baroroh Al Munawaroh; Al Hadi , Shofiana (CrossOver, 2025)
Strong influence from superhero is inspiring many sides to localize or create similar product by applying specific social culture. The phenomena of superhero localization can be seen through the product of Spiderman in Japan which uses the famousness of robot technology, creating Spiderman in robot shape. In India, Spiderman is localized using India’s cultural costume, and in Indonesia, Spiderman is localized into comic entitled “Laba-Laba Merah” that has extremely different aim from the original. Another Indonesian localization product is the Sitcom of Superhero Kocak produced by E-Motion Entertainment, which has not been discussed previously. Therefore, this research aimed to explore and reveal the localization strategy, the impacts on character equivalence, and the applying particular dominant related to the character of Sitcom. Several theories used were Localization Strategies (Van Leeuween and Suleiman, 2010), Narrative Identity (Paul Ricoeur, 1992), Character Equivalence (Petrucci, 2012), Sitcom TV Genres (Brett Mills, 2009), and the characteristic of superheroes (Nachbar & Lause, 1992). A descriptive-qualitative method was used and data were collected through the captures of western superheroes’ films and Superhero Kocak. Specifically, the captures taken were those that provided the nine characteristics of superheroes (Nachbar & Lause, 1992). According to the 60 data obtained, the results showed that, first, all western superheroes were localized by applying narrative-visual localization strategy. Second, narrative-visual localization strategy affected character equivalence and narrative identity to be shifted. Third, particular dominant localization of narrative-visual was applied in regard to the character of Sitcom. In conclusion, the application of narrative-visual localization strategy formed changes in character equivalence and narrative identity towards superheroes. It also caused a shift in message and purpose between western superheroes and Superhero Kocak. Superhero Kocak became a parody with the purpose as mere entertainment for people.